Human Cytomegalovirus UL144 Gene Polymorphisms in Congenital Infections - Picone, Olivier (American Society for Microbiology, 2005)
The human cytomegalovirus (HCMV) UL144 gene is a tumor necrosis factor-like receptor with the potential to affect HCMV virulence. HCMV strains display genetic variability in the UL144 region, and the analysis of a potential link between UL144 gene polymorphisms and disease severity has scarcely been studied. However, a correlation between the UL144 genotype and congenital-disease outcome has been reported in one previous study, with the observation that all asymptomatic infants had a single UL144 genotype. In order to confirm or refute this finding, we determined the UL144 polymorphisms of HCMV strains recovered from the amniotic fluids of 38 infected fetuses and compared them to HCMV strains obtained from 30 viremic adult controls. The UL144 sequences were distributed among five genotypes (A, B, C, AC, and AB), as previously described. We observed similar percentages of the three major genotypes A (37%), B (33%), and C (27%) in our population. The UL144 genotype distributions were similar among the group of infected adults and the group of infected fetuses and among symptomatic and asymptomatic fetuses (P < 0.05). In our series, all five UL144 genotypes could be vertically transmitted from mothers to fetuses, and all could cause symptomatic congenital infection. We concluded that determination of UL144 polymorphisms in cases of congenital infection is not relevant, since it is unlikely to help predict the outcome of the infection.